ANALISIS YURIDIS PENYALAHGUNAAN KEWENANGAN SISTEM PENGELOLAAN WAKAF YANG TRANSPARAN DAN AKUNTABEL DALAM PERSPEKTIF HAM - Nabila Salsabila; Ainun Najib (Fakultas Ilmu Sosial dan Humaniora, 2026)
Abuse of authority in waqf management is a common problem in Indonesia. This can be detrimental to society and violate human rights. Abuse committed by public officials, especially in institutions that manage waqf funds, such as the Indonesian Waqf Board (BWI), is a serious violation that not only impacts state finances but also violates the economic and social rights of the community as beneficiaries of waqf. Socially, abuse of authority in waqf management will have a serious impact on public trust. This study aims to analyze the abuse of authority in a transparent and accountable waqf management system from a human rights perspective. The research method used is a normative juridical method with a content analysis approach. The results show that abuse of authority in waqf management can take the form of corruption, misappropriation, and lack of transparency. The impact of abuse of authority can be in the form of losses to society and human rights violations. Therefore, a juridical analysis is necessary to regulate transparent and accountable waqf management. Effective supervision ensures that public funds are used according to their mandate and social objectives. Law Number 41 of 2004 concerning waqf was a significant milestone in strengthening the national waqf system. This law places great emphasis on productive and professional waqf management so that it can serve as an instrument for the economic development of the community.